Historical analysis of the type species of the genus Trichobilharzia Skrjabin et Zakharov, 1920 (Platyhelminthes: Schistosomatidae) - Aldhoun, Jitka; Kment, Petr; Horák, Petr (Zootaxa, 2016)
Trichobilharzia Skrjabin & Zakharov, 1920 is known as the most species-rich genus of the blood fluke family Schistosomatidae. To date, more than 40 species have been described, even though validity of some of them is questionable (Horák et al. 2002). Members of the genus use various birds as final hosts, but they attract attention mostly as causative agents of hypersensitive skin reaction (cercarial dermatitis or swimmer’s itch) in mammals including humans. As this is one of the